Second Harmonic Generation, Electrooptical Pockels Effect, and Static First-Order Hyperpolarizabilities of 2, 2′-Bithiophene Conformers: An HF, MP2, and DFT Theoretical Investigation. (16th December 2013) - Alparone, Andrea
Abstract : The static and dynamic electronic (hyper)polarizabilities of the equilibrium conformations of 2, 2′-bithiophene ( anti-gauche and syn-gauche ) were computed in the gas phase. The calculations were carried out using Hartree-Fock (HF), Møller-Plesset second-order perturbation theory (MP2), and density functional theory methods. The properties were evaluated for the second harmonic generation (SHG), and electrooptical Pockels effect (EOPE) nonlinear optical processes at the typicalλ = 1064 nm of the Nd:YAG laser. The anti-gauche form characterized by theS– C 2 – C 2 ′ –S dihedral angle of 137° (MP2/6-311G**) is the global minimum on the potential energy surface, whereas the syn-gauche rotamer (S– C 2 – C 2 ′ –S = 48°, MP2/6-311G**) lies ca. 0.5 kcal/mol above the anti-gauche form. The structural properties of the gauche structures are rather similar to each other. The MP2 electron correlation effects are dramatic for the first-order hyperpolarizabilities of the 2, 2′-bithiophenes, decreasing the HF values by ca. a factor of three. When passing from the anti-gauche to the syn-gauche conformer, the static and frequency-dependent first-order hyperpolarizabilities increase by ca. a factor of two. Differently, the electronic polarizabilities and second-order hyperpolarizabilities of these rotamers are rather close to each other. The syn-gauche structure could be discriminated from the anti-gauche one through its much more intense SHG and EOPE signals.